Duties, rights and afro-communitarian societies - Nyirenda, Nitumbiko (My University, 2019)
Human rights are at the center of most world societies today. The traditional assumption has been that they are necessary and universal. However, in light of their universality, there are variations with regard to a conception of human rights that each society has. That is, even if most societies acknowledge existence of human rights, how each society thinks about human rights, in terms of justification and application for example, may be different. In this paper, while presenting various African conceptions of human rights, I argue for a conception of human rights from the stand point of duties. I argue that human rights in Afro-communitarian societies are implicit within the language of duty. To understand the implicit nature of rights, I argue for rights as needs. I take human rights (as needs), to be the basic conditions for living a decent life in a society.
A Research Report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Arts, Philosophy, Johannesburg 2019
Keywords: Citizenship-South Africa; Human rights